Diode triggered ESD power clamp circuit with accurate discharge duration. Issue 11 (1st May 2016) - Yang, Zhaonian; Zhang, Yue; Yang, Yuan; Yu, Ningmei
Abstract : A new diode triggered power clamp circuit is proposed. It adopts diode strings to detect electrostatic discharge event and avoid mis‐triggering. By considering the amount of ESD charges in different power‐on ESD events, a compensation circuit with a new turn‐off mechanism is presented to accurately control the discharge duration, and this mechanism is validated by simulation. The circuit is fabricated in a 0.18 μm 1.8 V CMOS process, and the ESD performance is verified by the transmission line pulse measurement.